Acute inhibition of PMCA4, but not global ablation, reduces blood pressure and arterial contractility via a nNOS‐dependent mechanism. Issue 2 (30th November 2017) - Lewis, Sophronia; Little, Robert; Baudoin, Florence; Prehar, Sukhpal; Neyses, Ludwig; Cartwright, Elizabeth J.; Austin, Clare
Abstract: Cardiovascular disease is the world's leading cause of morbidity and mortality, with high blood pressure (BP) contributing to increased severity and number of adverse outcomes. Plasma membrane calcium ATPase 4 (PMCA4) has been previously shown to modulate systemic BP. However, published data are conflicting, with both overexpression and inhibition of PMCA4 in vivo shown to increase arterial contractility. Hence, our objective was to determine the role of PMCA4 in the regulation of BP and to further understand how PMCA4 functionally regulates BP using a novel specific inhibitor to PMCA4, aurintricarboxylic acid (ATA). Our approach assessed conscious BP and contractility of resistance arteries from PMCA4 global knockout (PMCA4KO) mice compared to wild‐type animals. Global ablation of PMCA4 had no significant effect on BP, arterial structure or isolated arterial contractility. ATA treatment significantly reduced BP and arterial contractility in wild‐type mice but had no significant effect in PMCA4KO mice. The effect of ATA in vivo and ex vivo was abolished by the neuronal nitric oxide synthase (nNOS) inhibitor Vinyl‐l ‐NIO. Thus, this highlights differences in the effects of PMCA4 ablation and acute inhibition on the vasculature. Importantly, for doses here used, we show the vascular effects of ATA to be specific for PMCA4 and that ATA may be a further experimental tool for elucidating the role of PMCA4.